Derivation of cloud top heights using HRIR data (MAUSAM, 1977)
Grid point temperatures derived from Radiance measurements of High Resolution Infra-Red sensors of Nimbus III were obtained from World Data Centre, Goddard Space Flight Centre, U.S.A. for specific areas on two selected days-7 Nov 1969 and 24 Jul 1969. The former is a day on which a severe cyclonic storm crossed the east coast of India near 17°N and the latter is a day on which monsoon was active generally over the country. The thermal fields were analysed and the cloud top heights derived in different sectors of the disturbed areas. The results have been discussed in terms of the synoptic situations and aerological data of nearby ground stations.